Penetrating Marjolin's ulcer of scalp with intracranial extension: A multidisciplinary experience - Mishra, Sudhansu Sekhar (Asian J Neurosurg, 2014)
Marjolin's ulcer invading the skull, dura mater, and the brain is quite exceptional. We report such a rare case of massive Marjolin's ulcer arising in the chronic scar tissue of the scalp of an elderly male. The ulcer had invaded the skull, dura mater, and underlying brain tissue. The patient was managed successfully by wide excision and scalp reconstruction. The importance of appropriate and timely wound management of scar ulcers with high malignant potential is highlighted. The role of multidisciplinary approach in the scalp reconstruction is discussed.